2021
DOI: 10.1002/adfm.202111351
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Doping Efficiency in Organic Semiconductors: Fundamental Principle and Promotion Strategy

Abstract: Molecular doping, a fascinating technique to modulate the electrical property of organic solids by importing additional charges, has been one of the focal points of active research over the last three decades. Due to the potential applications in clean energy and artificial intelligence, molecular doping is experiencing a second golden stage by virtue of its compatibility with solution‐processed organic functional devices. The central challenge at present promoting the doping efficiency. This perspective start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 114 publications
0
34
0
1
Order By: Relevance
“…4,8–10 However, a high doping level in BHJ layers is often undesired since the coulombic potential of dopant counterions can create additional traps and thereby diminish the long-range order of molecular packing, 11,12 which serves as a bottleneck to increasing electrical conductivity and preventing over-high dark carrier density. 13 In principle, n- or p-doping are both feasible in electron acceptors and donors, respectively, yet n-doping in OSCs is remarkably more challenging due to limited candidate dopants, mismatched energy levels and air instability. 4,8…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8–10 However, a high doping level in BHJ layers is often undesired since the coulombic potential of dopant counterions can create additional traps and thereby diminish the long-range order of molecular packing, 11,12 which serves as a bottleneck to increasing electrical conductivity and preventing over-high dark carrier density. 13 In principle, n- or p-doping are both feasible in electron acceptors and donors, respectively, yet n-doping in OSCs is remarkably more challenging due to limited candidate dopants, mismatched energy levels and air instability. 4,8…”
Section: Introductionmentioning
confidence: 99%
“…4,[8][9][10] However, a high doping level in BHJ layers is oen undesired since the coulombic potential of dopant counterions can create additional traps and thereby diminish the long-range order of molecular packing, 11,12 which serves as a bottleneck to increasing electrical conductivity and preventing over-high dark carrier density. 13 In principle, n-or p-doping are both feasible in electron acceptors and donors, respectively, yet n-doping in OSCs is remarkably more challenging due to limited candidate dopants, mismatched energy levels and air instability. 4,8 Since the Zhan group pioneered the design of the rst nonfullerene acceptor (NFA), 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)dithieno[2,3-d:2 0 ,3 0 -d 0 ]-s-indaceno[1,2-b:5,6-b 0 ]dithiophene (ITIC), in 2015, recent years have witnessed unparalleled advances in NFAs and their OSCs (namely, NF-OSCs), thanks to their tunable electronic structures and strong optical absorption in the visible and near-infrared bands compared to fullerene acceptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, molecular doping, which introduces extra holes (p-doping) or electrons (n-doping) via electrostatic induction or certain chemical reaction, has the potential to regulate these electronic defects. [17][18][19][20][21][22] It has been reported that the PCE values of doped OSCs were 17.1%The semitransparent and colorful properties of organic solar cells (OSCs) attract intensive academic interests due to their potential application in building integrated photovoltaics, wearable electronics, and so forth. The most straightforward and effective method to tune these optical properties is varying the componential ratio in the blend film.…”
mentioning
confidence: 99%
“…Alternatively, molecular doping, which introduces extra holes (p-doping) or electrons (n-doping) via electrostatic induction or certain chemical reaction, has the potential to regulate these electronic defects. [17][18][19][20][21][22] It has been reported that the PCE values of doped OSCs were 17.1%…”
mentioning
confidence: 99%